Caracterização de um handgrip com mola e um bracelete instrumentados com sensores FBG e aplicação dos dispositivos em um estudo de caso de fadiga muscular - Pereira, Fábio Santana (2022)
This work presents the characterization of a spring handgrip and a forearm band instrumented with sensors based on optical fiber Bragg gratings (FBGs) and application of these devices in a case study to assess muscle fatigue. Optical fiber sensors have been applied in biotechnology research, especially FBG, due to their ability to detect changes in temperature and mechanical loads. Optical fiber sensors have advantages such as reduced size, ease of implementation, being multiplexed, cost-effective and biocompatible. Handgrip force is a variable widely used in epidemiological studies. It is characterized as a predictor of a general health status of the subject and is considered a non-invasive method of assessment. There is a correlation between handgrip force and the intensity of muscle fatigue. In the present study, sensors based on FBGs were fixed on two devices, commercial handgrips and forearm bands. The demodulation technique consists of monitoring the variation of the Bragg wavelength of the grating when the subject performs a movement of flexion of the fingers pressing the instrument. After characterizing the instruments through mechanical assays, it is possible to relate the wavelength variations to handgrip forces. The handgrip apparatus with different loads were instrumented. The instrumented devices were evaluated in an in vivo case study, in the assessment of muscle fatigue during isometric contraction assays of maximum strength of the carpal flexor muscles of a single subject. Handgrip forces data as a function of the time were obtained for both, dominant and non-dominant, hands of the subject. The highest forces obtained were of the order of 160 N and are related to the non-dominant hand and the device with the highest load. Strain values were also obtained through the instrumented band and are related to variations in the forearm muscle volume. Maximum strain values of 4383,58 µε were obtained for the assays performed with the handgrip of the lowest load. Through these data, it was also possible to analyze muscle fatigue and its variation in relation to the load of the devices. The shortest fatigue times, 43 s, were obtained for the highest loads and for the non-dominant hand. These data agree with the exercise physiology literature.